Kualitas Isi dan Kalimat Efektif pada Teks Pidato Mendikbudristek di Peringatan Hari Pendidikan Nasional 2023 dan 2024 sebagai Bahan Ajar Membaca Siswa SMA kelas 10 - Iko Meifarindra Anugari; Awalina Putriyani; Wafiqotul Azizah; Tulus Eko Sriyandoyo; Muhammad Rizal Rusdi; Asep Purwo Yudi Utomo; Deby Luriawati Naryatmojo (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
The teaching material of a student can come from anywhere, one of which is an oration text. In an oration text, it is necessary to pay attention to the quality of content, effective sentences, and language suitability. This research aims to know the quality of content and language suitability contained in the Mendikbudristek oration text on National Education Day 2023 for a tenth-grade SMA student's teaching material. The method used in this research is a qualitative descriptive method. This qualitative descriptive method is used to investigate and explain matters related to a fact that occurs in the surrounding environment. Additionally, the data analysis in the study is conducted using the method of agih. The method of agih is a method where the determining tool is part of the language concerned. The result of this research is that there are still several errors in the Mendikbudristek oration text on National Education Day 2023 and 2024, including spelling errors, incorrect words, and word economy. This causes some sentences to be ineffective and the information provided is not well conveyed to the reader. It is hoped that this research can provide knowledge to readers so that they can understand language rules and linguistic norms, thus ensuring that the purpose of the provided information is well conveyed to the public.